Adopsi IFRS dan Pengaruhnya Terhadap Manajemen Laba Akrual dan Manajemen Laba Riil Pada Perusahaan Manufaktur Di Bursa Efek Indonesia - - Ismawati; Rita Yuliana; Yuni Rimawati (InFestasi, 2018)
This study aims to provide empirical evidence on adoption of IFRS and the effect toaccrual earnings management and real earnings management. This study usedmanufacturing firm data which is listing on Indonesia StockExchange in 2010-2013 and there are 63 firm used as sample. This study usedsecondary data. 2010 and 2011’s financial statement used to test descriptivestatistic at the beginning stage adoption of IFRS. 2012 and 2013’s financialstatement used to test descriptive statistic at the advance stage adoption of IFRS.The technique of data analysis in this study using multiple linear regressionanalysis. The result of this study find empirical evidence that IFRS adoption has negativeinfluence to accrual earnings management. This finding confirmation the result of descriptive statistic that accruals earnings management stage descend at the advance stage adoption of IFRS compared to the beginning stage adoption of IFRS.IFRS adoption doesn’t have influence to real earnings management through proxyas operation cash flow, production cost, and descretioner cost after firm adoptedIFRS at the beginning stage and also at the advance stage adoption of IFRS.